Pengaruh Digital Capability Dan Digital Literacy Terhadap Kinerja UMKM Di Tanjung Redeb - Nahwani Fadelan; Muslimin Muslimin; Lala Lala (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
This study aims to analyze the influence of digital capability and digital literacy on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Tanjung Redeb. MSMEs play a vital role in the Indonesian economy; however, digitalization presents both challenges and opportunities. A quantitative method was employed by collecting data through questionnaires. The findings reveal that both digital capability and digital literacy significantly affect the performance of MSMEs in Tanjung Redeb. Among the two, digital capability exerts a stronger influence on performance compared to digital literacy. The combined effect of digital capability and digital literacy also shows a significant impact on MSME performance, as evidenced by a significance value of 0.001 (less than 0.05) and a t-value of 5.278 (greater than the t-table value of 1.662). Furthermore, digital literacy independently has a significant effect on MSME performance in Tanjung Redeb, with a significance value of 0.001 and a t-value of 5.328 (also greater than the t-table value of 1.662). Together, digital capability and digital literacy significantly influence the performance of MSMEs in Tanjung Redeb, supported by a significance value of 0.001 (less than 0.05) and an F-value of 53.491 (greater than the F-table value of 3.09).